Prevalence of Musculoskeletal Disorders in Gardeners.: Life Sciences-Physiotherapy for better pain management - Rushikesh Rajendra Mangale; Dr. Smita Chandrakant Patil; Dr. Chandrakant Babaso Patil; Dr. Khushboo Trishant Chotai (International Journal of Life Science and Pharma Research, 2022)
Musculoskeletal disorders are a group of disorders that affect the musculoskeletal system involving the nerves, tendons and ligaments as well. Musculoskeletal disorders are emerging common health problems among workers due to intensive manual work. They include shoulder pain, tenosynovitis, carpal tunnel syndrome etc..Occupations with prolonged work hours and repetitive tasks are one of the main reasons for development of abnormal posture and micro injury to the muscles. Gardening is a profession where multiple positions are assumed that are required to be maintained over long periods of time eg squatting position or trunk bent position. Also, repetitive movements of the wrist and hand are used. Gardening is also a profession which has not been given much attention by the medical field and hence their postural and muscular abnormalities which are a result of labour intensive and cumbersome work are often overlooked. These problems can easily be dealt with if proper physiotherapy is done. Therefore, keeping in mind the workload of this target group. it is important to rule out the musculoskeletal abnormalities faced by them. So the present study was conducted with the aim to determine prevalence of musculoskeletal disorder among women gardeners. An observational study was conducted in 60 female gardeners at Krishna hospital Karad. Only women within the age group of 20-60 years were involved. As the outcome measure, visual analogue scale (VAS) was used to rate the intensity of pain or discomfort experienced by the gardeners. They were presented with a standard VAS and asked to mark their perceived amount of discomfort. Nordic pain questionnaire was also used to determine the sites of pain and also the duration of symptoms. The results of the study indicated that lower back pain was more prevalent in female gardeners of Krishna Hospital which is attributed to the nature of their work followed by neck problem 43.33%, knee problem 40%, wrist problem 31.66%, and shoulder problem 28.33%. Therefore it can be concluded that musculoskeletal disorders are prevalent in female gardeners with low bak pain being the most common.